Synaptic devices towards neuromorphic electronics - Datta, Indira (Nanyang Technological University, 2024)
New research has introduced neuromorphic systems that use artificial synapses as devices to carry out the development of platforms for interfacing biological tissues. These cutting-edge transistor-based synaptic systems offer a range of advantages including increased stability, controllable parameters, clear operation mechanisms, and construction material versatility. Concurrent learning is a huge advantage of these systems, enabling synaptic weight updates without signal transmission interruption, as well as facilitating synergistic control which allows the building of robust neural networks with fewer elements. Previously, researchers investigated a variety of materials capable of serving as artificial synapses for research and development in the field of neuromorphic computing. Magnetic multilayer structures have been viewed as highly promising materials as storage mediums for magneto-optoelectronic recording, especially Cobalt-Platinum (Co-Pt) multilayers [easily produced using DC and RF Magnetron sputtering]. The Electrolyte (DEME-TFSI) is electrically insulating but ionically conductive, so free ions wander in response to an applied gate voltage. Over the course of this Final Year Project, metallic multilayers and gate electrolytes have been examined and tested to identify potential neuromorphic electronic solutions. This report examines potentially brain-like structures and their cognitive behaviour including learning, forgetting, and relearning, as well as synaptic behaviour such as short and long-term plasticity. Area Transfer curves, gate voltage hysteresis loops, and multilevel resistance modulation were studied, and biological functions including long-term potentiation and Depression (LTP and LTD), Excitatory and Inhibitory Postsynaptic Current (EPSC and IPSC), Spike Amplitude and Duration Dependent Plasticity (SADP and SDDP), Paired Pulse Facilitation and Depression (PPF and PPD), and repeated learning and forgetting curves were emulated by our novel device. Furthermore, these functions are regulated by gate voltage application, such as by varying pulse number, interval, duration, and amplitude.